Analysis of Students’ Learning Motivation Using a Virtual Laboratory During Covid-19 ‎Pandemic on Hooke’s Law - Faris, Muhammad; Dwikoranto, Dwikoranto (Universitas Negeri Surabaya, 2021)
Since the spread of the Covid-19 outbreak, the world of education in Indonesia has faced difficult situation. Namely, it is mandatory to carry out online learning to reduce the impact of the spread of the Covid-19 virus. However, with the implementation of online learning, there is a decrease in student learning motivation so that an alternative is needed to generate student learning motivation, by using a virtual laboratory as a supporting medium. This research uses quantitative research with an accidental sampling method, with a population of science highschool from XI and XII grade students who are conducting online learning. The data analysis method uses non-parametric Mann-Whitney U statistics and measures student learning outcomes in Hooke's Law with a virtual laboratory. The results showed that by using a virtual laboratory students' learning motivation increased from online learning in general, because the p-value is 0.000 which p < 0.05 means there is a significance changes. Students wih higher learning motivation score better than students with lower motivation . With the average score in a row from medium, high, and very high motivation is 39.29; 43.70; 44.00 from the maximum score 100.